Does the Prevention of Illegal Eviction From and Unlawful Occupation of Land Act of 1998 Provide Adequate Family Home Protection to Insolvent Debtors or Is It Still Pie in the Sky? (Part 1) - Boraine, André (Obiter, 2020)
Although some legal systems provide some protection of the homestead or family home for the debtor when his or her estate is insolvent, such direct protective measures are absent in South African insolvency law. Such protection during insolvency can be provided by means of some level of exemption of the family home or homestead of the insolvent like in the insolvency laws of the USA, or by providing protection of occupancy to the insolvents and his or her dependants as is the case in England and Wales.In view of the developments in light of the right to housing as provided for in section 26 of the Constitution concerning the protection of the primary residence of a debtor in South African individual debt collecting and execution procedures, the question will be posed in Part 1 of this article if the same principles should apply in the case of a court hearing an application for compulsory sequestration, especially if the debtor raises the point that the sequestration order may render him or her homeless, should also be considered by such court. In this respect, no direct authority for this proposition could be found yet. (Commentators have argued for some time that the position of the homestead of the debtor in insolvency needs attention of the legislature as well but there has not been real progress in this regard to date.)However, there are a few judgments where the applicability of the Prevention of Illegal Eviction from and Unlawful Occupation of Land Act 19 of 1998 (the PIE Act) after sequestration of the insolvent’s estate has been considered. Part 2 of the article will therefore be devoted to discuss developments in this regard and to consider what problems are encountered in applying the PIE Act during insolvency of the debtor and also if this Act provides sufficient protection to insolvent debtors to prevent them from being evicted from “their” homes where they cannot afford alternative accommodation.Against this background, the two parts of the article deal with different aspects of the issue under discussion. Ultimately the two parts are thematic to provide some answers to the pertinent question, namely if the PIE Act can provide effective interim and/or adequate protection to an insolvent debtor who may be evicted from his or her (former) homestead – in particular in the absence of direct measures in insolvency law, which protect insolvents and their dependants under these circumstances. In raising this question pertinent issues regarding the application of the PIE Act in insolvency also will be considered.